Without mandatory regulation, clinical physiologists put patients at risk. (13th January 2015) - Casey, Amanda
Abstract : The professionals who maintain medical devices are unregulated, meaning that investigation of potential malpractice may never occur and that anyone can use the title "clinical physiologist." Amanda Casey calls for statutory regulation